Implementasi Shalat Dzuhur Berjamaah Dalam Membentuk Kedisiplinan Belajar Siswa Di SDIT Al-Muddatsiriyah Kemayoran Jakarta - Marjuki AlJawi; Fransiska Ulandari; Sabariah Sabariah (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2022)
The aim of the researcher is to identify and describe the implementation of the congregational midday prayer in shaping student learning discipline at SDIT Al-Muddatsiriyah Kemayoran, Central Jakarta. This study uses a qualitative descriptive approach with descriptive analysis techniques. In the process of collecting data, researchers used the method of observation, interviews and documentation. The results of the study show: (1) the congregational midday prayer is a school effort in shaping students' prayer discipline. (2) evaluating the congregational midday prayer using the Mutaba'ah book so that students are disciplined and honest. (3) students who are disciplined to pray dzuhur in congregation will form learning discipline at school. This research can be a positive input for SDIT Al-Muddatsiriyah to pay more attention to the technical implementation of the congregational midday prayer.